In Znaniecki’s culturalist philosophy - Niebrój, Katarzyna (Folia Philosophica, 2000)
According to Protagoras: „Man is the measure of all things, of those which exist, in that they exist, and of those which do not exist, in that they do not exist”. Usually, the interpretation of this is limited to its gnosiological or axiological aspects, but it is possible to interpret it by emphasising that the object to which the said measure should be applied is the existence or non-existence of things. In this sense, Protagoras’s statement describes man as the measure of being, and the whole problem is transposed to a metaphysical plane. According to Znaniecki, man is both the centre, measure, and principle and the centre, measure, and principle of himself - thus the Polish philosopher returns to Protagoras's thesis that man is the measure if everything. Znaniecki claims that no order exists, and in this sense no reality, that would not be man’s work, including man himself. Individuals as creators are not subjugated to anything. It is the creative individuals that constitute, both for reality and for themselves as elements of that reality) what is and either would not be what it is, or would not be what it is.